Prenatal methadone exposure produces functional and molecular alterations in the basolateral amygdala and decreased voluntary ethanol intake in female, but not male offspring - Gamble, Meredith E.; Montero, Michelle; Silberstein, Dana N.; Deak, Terrence; Varlinskaya, Elena I.; Diaz, Marvin R. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionA result of the ongoing opioid epidemic has been a significant rise in the rates of opioid use during pregnancy. This includes use of maintenance medications for opioid use disorder (MOUDs), such as methadone, which are the standard of care for pregnant people with an opioid use disorder (OUD). Although the use of MOUDs leads to better neonatal outcomes in exposed offspring compared to those born from individuals with untreated OUD, the pharmacology of MOUDs is similar to misused opioids. Despite the high prevalence of prenatal exposure to opioids, including MOUDs, our understanding of the long-term consequences of these exposures in offspring is limited. Prenatal drug exposure is known to be a risk factor for future substance use disorder and mood disorders, yet, how prenatal opioid exposure influences ethanol intake in adult offspring and associated affective behaviors has not been examined.MethodsUsing a rat model of prenatal methadone exposure (PME), which included twice daily methadone injections from gestational day 3-20, this study assessed ethanol intake in adult offspring and how exposure to forced swim stress (FSS) altered ethanol intake, in addition to examination of depressive-like behavior during the FSS. Given the role of the basolateral amygdala (BLA) in emotion and reward processing, we also conducted patch clamp electrophysiology experiments from BLA neurons to investigate changes in synaptic transmission and gene expression of neuromodulatory systems that are known to influence emotion and reward processing.ResultsFemales with a history of PME consumed less ethanol than control females, with no effects of PME on ethanol intake evident in males. While PME increased immobility during FSS in both males and females, FSS had no effects on ethanol intake. PME increased glutamate transmission and altered dopamine D1, D2, and D3 receptor and mu opioid receptor mRNA in the BLA of females, but not in males.DiscussionCollectively, this study identified impairments in emotion and reward processing, in addition to alterations in synaptic function and gene expression in the BLA of females with a history of PME, supporting previous findings from our lab demonstrating that female offspring are more sensitive to the long-term effects of PME.